Assessment Of Genetic Variation Among Three Species Of Aerides, An Epiphytic Orchid From Western Ghats, India Using Rapd Markers - NAGANANDA. G. S; CHETANA. G. R; RAJATH. S; SANDEEP SURYAN; S. SUNDARA RAJAN (International Journal of Pharma and Bio Sciences, 2012)
The genetic diversity and relationship between the different species of genus Aerides i.e, A.crispa, A. maculosa and A. ringens was determined using randomly amplified polymorphic DNA (RAPD) analysis. All three species were collected from Western Ghats of India and analyzed using ten RAPD primers. Total of 159 RAPD fragments were generated of which 40 were polymorphic. The Jaccard’s similarity coefficient values ranged from 0.5 between A.crispa and A.ringens to 0.66 between A. crispa and A. maculosa. The analysis included both total and polymorphic band scores. A dendrogram tree was constructed using UPGMA method depending on similarity coefficient values. In this study, the three different species of genus Aerides were successfully differentiated by RAPD method. The results obtained could help in better understanding of the genetic profile and variation among these species and can be used to develop strategies for conservation, population and evolutionary genetics studies of these species.